Two new species of Trevathana (Crustacea, Cirripedia, Balanomorpha, Pyrgomatidae) from the Western Indian Ocean and French Polynesia - Achituv, Yair; Langzam, Yaakov (Zootaxa, 2009)
Two new species of the Pyrgomatid barnacle Trevathana are described: Trevathana synthesysae nov. sp., extracted from Plesiastrea versipora from the Indian Ocean Islands Réunion and Mauritius, and Trevathana isfae nov. sp. from a colony of Favia stelligera from French Polynesia, which, until recently, was terra incognita with regard to coral-inhabiting barnacles. The two new species are distinctive by their relatively broad scutum as compared to Trevathana dentatum, their prominent adductor ridge extending beyond the basal margin of the scutum, and their quadrangular tergum.